INDONESIA-TÜRKIYE EDUCATION AND WORK OPPORTUNITIES - Nurullah (POLITEKNIK LP3I JAKARTA, 2026)
This article examines work and education opportunities in Türkiye within the context of Indonesia-Türkiye strategic partnership. It is developed from Nurullah's presentation material that highlights more than 75 years of diplomatic relations, Türkiye's strategic location, priority investment sectors, higher education ecosystem, and future-oriented technology careers. Using a qualitative conceptual review approach, the article synthesizes the presentation content with previous Scopus-indexed studies on higher education internationalization, employability, innovation systems, and future work. The discussion shows that Türkiye offers strategic value for Indonesian students, universities, entrepreneurs, and policy actors through quality education, international student mobility, investment opportunities, technology-driven sectors, and university-industry collaboration. The article argues that Indonesia-Türkiye cooperation should move beyond symbolic diplomacy toward structured academic mobility, joint research, internship pathways, entrepreneurship programs, and future-skills development. The implication is that higher education institutions need to position international cooperation as a bridge between education, employment, innovation, and sustainable development.